Interleukin-20 Gene Polymorphism and Serum Levels of Interleukin-20 and Interleukin-23 in Rheumatoid Arthritis - Iman Najat Ali; Najat Jabbar Ahmed Berwary (Diyala Journal of Medicine, 2025)
Background: Rheumatoid arthritis (RA) is an autoimmune disease marked by complex causes and ongoing joint inflammation. Recently, more efforts have been directed at finding new non-invasive prognostic biomarkers for RA, which can help in disease monitoring. Objectives: To investigate the circulatory levels of IL-20 and IL-23 in RA patients relative to healthy volunteers and to evaluate their correlation with disease activity. Additionally, to explore the association between IL-20 genetic polymorphism and RA susceptibility. Patients and Methods: The study comprised a total of 85 individuals with RA and 45 healthy subjects. IL-20 and IL-23 concentrations were measured using ELISA, and disease activity was assessed using the DAS-28 score. The IL-20 rs2981573 polymorphism was genotyped using Amplification Refractory Mutation System-Polymerase Chain Reaction. Results: The study found that RA participants exhibited significantly elevated serum IL-23 levels compared to controls (P = 0.0347), while IL-20 levels did not differ (P = 0.6354). Correlations between IL-20 and IL-23 with DAS-28 were significant (P = 0.0021 and P = 0.0030, respectively). Regarding the IL-20 gene polymorphism, no significant association was found between the rs2981573 gene polymorphism and RA susceptibility Conclusion: This study demonstrated that IL-23 levels were significantly higher in RA patients and may have diagnostic value. Although IL-20 levels were not significantly different between groups, both cytokines showed a positive correlation with disease activity and could be valuable markers. Furthermore, the IL-20 gene polymorphism showed no association with rheumatoid arthritis susceptibility. Keywords: IL-20 Genetic polymorphism, DAS-28, rheumatoid arthritis, IL-20, IL-23.